Manajemen Produktivitas Sumber Daya Manusia: Analisis Pengaruh Pelatihan, Kompensasi, Lingkungan Kerja, dan Motivasi terhadap Produktivitas Karyawan - Furqon Furqon; Shabrina Aisyah; Sulaeman Sulaeman; Wahyudi Wahyudi (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Human Resource Management (HRM) plays a strategic role in enhancing organizational productivity through effective management of human capital. This study aims to analyze the influence of training and development, compensation, work environment, and work motivation on employee productivity. The research employed a quantitative approach using a survey method. The population consisted of employees at manufacturing companies in Banten Province, with a sample of 120 respondents selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using multiple linear regression. The results showed that training and development (t = 4.071; sig. = 0.000), compensation (t = 3.397; sig. = 0.001), work environment (t = 3.384; sig. = 0.001), and work motivation (t = 3.046; sig. = 0.003) each had a significant positive effect on employee productivity. Simultaneously, the four independent variables explained 67.4% of the variance in productivity (R² = 0.674; F = 59.821; sig. = 0.000). These findings underscore the importance of integrated HRM practices in improving employee productivity and organizational competitiveness.